87. Anodal transcranial direct current stimulation of motor cortex does not ameliorates spasticity in multiple sclerosis. Issue 1 (January 2015) - Iodice, R.; Manganelli, F.; Ruggiero, L.; Dubbioso, R.; Santoro, L.
<x xml:space="preserve">Abstract</x> Spasticity is a common disorder and a major cause of a long-term disability in patients with multiple sclerosis (MS). Transcranial direct current stimulation (tDCs) is a potential tool to improve motor deficits in several neurological disease and, recently, it has been proposed as effective in decreasing spasticity after stroke. To assess whether anodal tDCS is effective in modulating lower limb spasticity in MS patients. We performed a single-centre randomized, double-blind, sham-controlled study to investigate efficacy of anodal vs sham tDCs in 20 relapsing-remitting MS patients. Ten patients received anodal tDCS stimulation to the primary sensorymotor cortex of the more affected side, 20 min for day, 5 days per week, for 2 weeks. Ten patients received sham tDCS stimulation. Spasticity was assessed by using the modified Ashworth scale (MAS) and the self-scoring MSSS-88 at baseline and at the end of protocol stimulation. No significant change in lower limb spasticity was observed for both anodal and sham tDCS stimulation. Anodal tDCS seems to be not effective in decreasing lower limb spasticity in MS patients.